Compression stiffness evaluation of polycaprolactone‐amorphous calcium phosphate 3D‐designed scaffolds oriented by finite element analysis - Liu, James; Roque, Renan; Barbosa, Gustavo Franco; Malavolta, Alexandre Tácito (Journal of applied polymer science, 2021)
Scaffolds are implants used to accelerate bone regeneration process, being a relevant element of research in bone tissue engineering field. In this context, the proposal of this research was to perform a mechanical behavior evaluation, by finite element analysis (FEA), of two different configurations of 3D scaffolds fabricated in a type of composite material of PCL‐ACP (polycaprolactone and amorphous calcium phosphate). The numerical results were compared with the experimental data and also, used to determine the compression stiffness of each studied scaffold configuration. Thus, it was possible to conclude that FEA is a tool that helps understand complex problems while being able to reduce time and cost in analysis, resulting in more efficient and less invasive medical procedures and treatments. In addition, the novelty of this multidisciplinary research work contributes as an application in tissue engineering area by relating a PCL‐ACP biomaterial with one unprecedented geometry of scaffold faced to FEA mechanical evaluation. Therefore, demonstrating to be a relevant subject for science by not only providing procedures that increases people's life quality but also for being a new application. Mechanical behavior of PLC‐ACP 3D printed scaffolds, according to stress analyzes performed by Finite Element Analysis (FEA) method. It presents the displacements and von Mises stresses obtained from the solutions, being possible to observe the deformations and the most critical stress points on the scaffolds.